2010
DOI: 10.1007/s12098-010-0087-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and psychosocial functioning of HIV infected children

Abstract: The quality of life and psychosocial functioning is reasonably good in children with HIV infection. Thus, we should strive to maintain and optimize the overall quality of life of these children so that they can have a productive and meaningful future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
4
23
1
Order By: Relevance
“…This was in accordance with multiple prior published studies, which reported that HIV infection significantly compromised HRQoL in children [20,29,30]. In the Indian context, HIV-related discrimination is often not limited to the infected individual, and social ostracism frequently involves the entire family [31].…”
Section: Discussionsupporting
confidence: 90%
“…This was in accordance with multiple prior published studies, which reported that HIV infection significantly compromised HRQoL in children [20,29,30]. In the Indian context, HIV-related discrimination is often not limited to the infected individual, and social ostracism frequently involves the entire family [31].…”
Section: Discussionsupporting
confidence: 90%
“…Parent proxy report of PedsQL TM 4.0 Generic Core (Hindi) was used for assessment of HRQOL of retinoblastoma survivors and siblings. The Hindi version of this questionnaire has been validated previously . The questionnaire consists of four essential core domains for pediatric HRQOL measurement: physical (eight items), emotional (five items), social (five items), and school (five items) .…”
Section: Methodsmentioning
confidence: 99%
“…4 Even though the survival was prolonged by ART there are at risk of impaired psychosocial functioning as their lower scores on total competence in youth (11-18 years) self report. 9 In contrast a quality of life study conducted among Indian children revealed that they have a better psychosocial and school functioning scores than children with cystic fibrosis 5 HIV children with normal CD4 count and undetectable viral load had school (51%) and dropout (28.6%), 10 they have compromised executive function and information processing, 11 81% systematic review reported some form of cognitive delay. 12 Children aged between 9-16 years in a study reported two third of the youth had met the criteria for at least one psychiatric disorder based on their youth versions of diagnostic interview schedule for children (DISC -IV).…”
Section: Discussionmentioning
confidence: 96%
“…3 The quality of life assessment studies among the children with HIV infection showed that their physical, psychosocial and school functioning was affected. [4][5][6] People living with AIDS and cancer experience stress, stress influences the number of immune cells and cytokine dysregulation. The practice of yoga, meditation, muscle relaxation, hypnosis was shown the effect of reducing the psychological and physiological effect of stress in cancers and HIV infection.…”
Section: Introductionmentioning
confidence: 99%